2017
DOI: 10.3920/jiff2017.0002
|View full text |Cite
|
Sign up to set email alerts
|

Survey of edible insect consumption in south-eastern Nigeria

Abstract: Edible insect consumption called entomophagy is very important in ensuring food security especially in a developing country like Nigeria, but promotion of entomophagy after a long period of adoption of western diets demands a comprehensive inventory of edible insect consumption in the past. At present, there is little or no repository of document with comprehensive information on edible insects consumed in the south eastern states of Nigeria and methods of use is also scarce in literature. It becomes imperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 11 publications
11
40
0
Order By: Relevance
“…This finding corroborates the reports of Ebenebe et al (2015), from the South-Eastern Nigeria; that insects eating were greatly associated with poverty as the rich/elites dropped the habits for the poor and the so called illiterates in the rural communities.…”
Section: Perception Of Edible Insects Farmingsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding corroborates the reports of Ebenebe et al (2015), from the South-Eastern Nigeria; that insects eating were greatly associated with poverty as the rich/elites dropped the habits for the poor and the so called illiterates in the rural communities.…”
Section: Perception Of Edible Insects Farmingsupporting
confidence: 82%
“…For instance, FAO (2008) as cited in Ebenebe and Okpoko (2015) recommended consumption of 34g of animal protein per person per day for normal growth and development. However, animal protein consumption in Nigeria stands averagely at 7-10g/person/day as a result of high poverty level and ignorance (Ebenebe and Okpoko, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several traditional edible insect cooking techniques, including steaming, roasting, smoking, frying, stewing, and curing (see Figure 2; Ebenebe et al, 2015;Graboswski & Klein, 2017;Lautenshläger et al, 2016;Nonaka, 2009;Obopile & Seeletso, 2013;Ramos-Rostro et al, 2016;Shockley, Lesnik, Allen, & Muñoz, 2018). These techniques are preceded by blanching to reduce foodborne microorganism counts and to inactivate enzymes (Marshall, Dickson, & Nguyen, 2016).…”
Section: (House Crickets)mentioning
confidence: 99%
“…Previous Nigerian studies have suggested affordable and available protein-rich foods such as rabbit meat (55) , insects (56) , wild plant species (57) , indigenous leafy vegetables (12) and goat milk (58) . Some studies have already been conducted on determinants (for example, socio-economic factors, education, infections) of protein intake and PEM, and it is advised to extend Table 11.…”
Section: Recommendations and Future Researchmentioning
confidence: 99%